Pathways to climate-neutral shipping: A Danish case study. (1st December 2019) - ben Brahim, Till; Wiese, Frauke; Münster, Marie
Abstract: In this paper, we describe pathways for the Danish maritime cargo sector to achiev CO2 e (equivalent) neutrality by 2050 in compliance with the Paris Agreement. In the approach of our model, we not only include national greenhouse gas emissions, but also suggest a method for assigning greenhouse gas emissions from international shipping to countries. Our modelling results indicate either that strong regulatory carbon budgets or a carbon price of at most 350–450 €2016 /t CO2 e would be necessary to induce this urgently needed transition. This would double today's average cargo transport costs, while increasing average import values by only 6–8%. Regarding fuel technologies, hydrogen, methanol and ammonia are the most suitable from a socio-economic cost perspective, though, due to the high cost uncertainties, there is no clear winner. Liquefied natural gas as an alternative intermediate solution would only have a short window of opportunity, due to methane leakage causing high greenhouse gas emissions as well as high fuel and technology costs. In so far as this gaseous fuel is based on renewable sources it can play a role, but only if methane leakage is drastically reduced. At present battery storage is only an option for short ranges. Highlights: Hydrogen, methanol, ammonia seem most compatible for carbon neutral shipping Liquefied natural gas only has a very short window of opportunity Methane leakage reduction is crucial for alternative carbon based marine fuels A carbon price of at most 350 - 450 €2016 per tCO2e would be necessary